Investigating Vertical and Horizontal Force-Velocity Profiles in Club-Level Field Hockey Athletes: Do Mechanical Characteristics Transfer Between Orientation of Movement? - Dylan Hicks; Claire Drummond; Kym Williams; Roland van den Tillaar (International Universities Strength and Conditioning Association, 2023)
To inform physical preparation strategies in field hockey athletes, this cross-sectional study investigated the transfer of mechanical characteristics in different force-vectors and determined the correlations between vertical and horizontal force-velocity profiles and performance outcomes. Thirty-one club-level field hockey athletes (age: 23.1 ± 4.3yrs, body mass: 70.6 ± 10.3kg, height: 1.72 ± 0.09m) performed vertical (jump) force-velocity profiles by performing countermovement jumps at three incremental loads, and horizontal (sprint) force-velocity profiles by performing maximal 30-meter sprint efforts. When comparing matched mechanical variables between F-v profiles in each force orientation, small to moderate significant correlations (0.37 ≤ r ≥ 0.62, p ≤ 0.03) were observed for relative theoretical maximal force (F0), power (PMAX) and theoretical maximal velocity (v0). The performance outcomes of both F-v profiles highlighted a large, significant negative correlation (r = -0.86, p = 0.001) between variables. Multiple linear regression analysis of F-v profiles identified F0 and v0 accounted for 74% and 94% of the variability in jump height and sprint time respectively, however v0 appeared to be a greater predictor of both performance outcomes. Due to the significant relationships between variables, the results of this study suggest vertical and horizontal F-v profiling explain the same key lower-limb mechanical characteristics, despite the orientation of the movement task. With club-level field hockey athletes, coaches could therefore use mechanical profiling methods interchangeably and prescribe physical preparation interventions to assess neuromuscular function plus mechanical strengths and weaknesses by performing one force-velocity assessment only.